The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1098/rspb.2001.1882
|View full text |Cite
|
Sign up to set email alerts
|

Brighter yellow blue tits make better parents

Abstract: Whether or not bird ornaments are a signal for direct (e.g. good parents) or indirect (e.g. good genes) benefits to prospective partners in sexual selection is controversial. Carotene coloration in Parus species is directly related to the ingestion of caterpillars, so that a brightly carotene-coloured tit may be signalling its ability to find caterpillars, a main high-quality food source for good fledgling development, and hence its parental abilities. If carotene-based plumage coloration is related to the goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
112
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 60 publications
4
112
2
1
Order By: Relevance
“…Birds being able to develop a conspicuous plumage during the moult could show a better health status in the next spring, especially because most of these blood parasite infections are chronic with birds suVering relapses while breeding (ValkiĂ­nas 2005). Birds in poor health would be less eYcient in acquiring carotenoid-rich food (Hill 1991(Hill , 1992Senar et al 2002) and consequently would exhibit a paler plumage. A previous experiment in the same study population showed that females medicated with primaquine did not vary in body condition during the breeding season, whereas body condition was reduced in control females during the same period, suggesting that blood parasites have negative eVects on female condition (Merino et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Birds being able to develop a conspicuous plumage during the moult could show a better health status in the next spring, especially because most of these blood parasite infections are chronic with birds suVering relapses while breeding (ValkiĂ­nas 2005). Birds in poor health would be less eYcient in acquiring carotenoid-rich food (Hill 1991(Hill , 1992Senar et al 2002) and consequently would exhibit a paler plumage. A previous experiment in the same study population showed that females medicated with primaquine did not vary in body condition during the breeding season, whereas body condition was reduced in control females during the same period, suggesting that blood parasites have negative eVects on female condition (Merino et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…As our methods of colour estimates had reasonably low measurement error to suYciently describe inter-individual diVerences in carotenoid chroma [repeatability (Lessells and Boag 1987) of two consecutive measurements R i = 0.66, F 13,14 = 4.83; P < 0.01], just one spectral measurement was taken from each individual in 2007. As in other studies based on the use of spectrophotometers not including UV reXectance (Figuerola et al 1999;Senar et al 2002;Hidalgo-GarcĂ­a 2006;Ferns and Hinsley 2008), we face a potential problem since blue tit visual perception extends into the UV range of the spectrum (Hunt et al 1998;Örnborg 2002). However, our main aim is to explore whether carotenoid chroma as experienced by human observers is associated with some health parameters of birds.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, in the study by Delhey et al (2003), it was in fact the less ornamented males that gained extra-pair offspring, so these results were inconsistent with the other studies supporting indirect models, in that the sign of the correlation was in the opposite direction. Evidence of a role for direct benefits in the blue tit comes from studies in which the carotenoid based coloration of foster males was correlated with the body size of their foster chicks (Senar et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…As carotenoids are not only used for coloration, but also play an important role in many physiological processes (Olson and Owens 1998), variation in carotenoid-based coloration is often considered to be a reliable predictor of individual quality. For example, individuals with plumage that contains more carotenoids are healthier (e.g., HĂ”rak et al 2001;Saks et al 2003b), survive better (Hill 1991;HĂ”rak et al 2001), are in better nutritional condition (Hill and Montgomerie 1994), or provide more care for their young (Senar et al 2002).…”
Section: Introductionmentioning
confidence: 99%